2017
DOI: 10.1016/j.celrep.2017.11.097
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of H3K4me3 at Transcriptional Enhancers Characterizes Acquisition of Virus-Specific CD8+ T Cell-Lineage-Specific Function

Abstract: Infection triggers large-scale changes in the phenotype and function of T cells that are critical for immune clearance, yet the gene regulatory mechanisms that control these changes are largely unknown. Using ChIP-seq for specific histone post-translational modifications (PTMs), we mapped the dynamics of ∼25,000 putative CD8 T cell transcriptional enhancers (TEs) differentially utilized during virus-specific T cell differentiation. Interestingly, we identified a subset of dynamically regulated TEs that exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
94
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(94 citation statements)
references
References 48 publications
(74 reference statements)
0
94
0
Order By: Relevance
“…While the proportion and number of mature, naive CD8 + T cells was not impacted in Kdm6b shRNA transgenic mice, upon IAV infection, fewer splenic D b NP 366 and D b PA 224 specific CD8 + T cells were observed at the peak of the IAV immune response. We have previously demonstrated that loss of H3K27me3 is a major consequence of virus-specific CD8 + T cell activation (15)(16)(17). Importantly, we identified a subset of gene promoters that exhibited bivalency for both H3K4me3 and H3K27me3.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…While the proportion and number of mature, naive CD8 + T cells was not impacted in Kdm6b shRNA transgenic mice, upon IAV infection, fewer splenic D b NP 366 and D b PA 224 specific CD8 + T cells were observed at the peak of the IAV immune response. We have previously demonstrated that loss of H3K27me3 is a major consequence of virus-specific CD8 + T cell activation (15)(16)(17). Importantly, we identified a subset of gene promoters that exhibited bivalency for both H3K4me3 and H3K27me3.…”
Section: Discussionmentioning
confidence: 71%
“…When a naïve CD8 + T cell differentiates into an effector CD8 + T cell, dramatic epigenetic changes occur to allow for the expression of lineage specific effector function (14)(15)(16)(17). As seen upon naïve CD4 + T cell activation, antigen-specific CD8 + T cell differentiation is associated with the rapid resolution of bivalency at fundamental transcription factor loci to a permissive epigenetic signature (16).…”
Section: Introductionmentioning
confidence: 99%
“…Despite our earlier observations demonstrating that rapid removal of H3K27me3 is a key outcome of naive, virus-specific CD8 + T cell activation (Denton et al, 2011; Russ et al, 2014; Russ et al, 2017), there is little understanding of the molecular mechanisms by which removal of H3K27 facilitates CD8 T cell differentiation. Moreover, the respective roles of KDM6A and KDM6B in mediating H3K27me3 removal remain wholly unknown.…”
Section: Introductionmentioning
confidence: 81%
“…Histone PTMs contribute to regulation of transcription by providing a platform that promotes binding of TFs and chromatin remodelling proteins (Kouzarides, 2007). We and others, have demonstrated that virus-specific CTL differentiation is associated with genome wide changes in chromatin accessibility and PTMs (Denton et al, 2011; Northrop et al, 2008; Russ et al, 2014; Russ et al, 2017; Scott-Browne et al, 2016; Sen et al, 2016; Wang et al, 2018; Wei et al, 2009; Zediak et al, 2011). More recently, extensive changes in chromatin accessibility, indicative of transcriptional activation was shown to occur prior to first cell division, and was dependent on RUNX3 (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation